THE NEIGHBORHOOD LEVEL SURVEY BY ADAPTING THE HEALTHY INDONESIA PROGRAM WITH FAMILY APPROACH'S (PIS-PK) INDICATORS - Ifroh, Riza Hayati; Ramdan, Iwan Muhamad (Universitas Negeri Gorontalo, 2024)
Some of the post-pandemic challenges in urban and rural areas are increasing efforts for clean and healthy living at the family level in tropical rainforest areas. The novelty of this research is that it conducted a household survey based on the indicators of the Healthy Indonesia Program with a Family Approach (PIS-PK). The study aims to identify the characteristics of the community in Samarinda City and measure differences in the practice of clean and healthy living behavior at the household level using the developed PIS-PK indicators. The research method uses a cross-sectional survey at the household level and determines specific locations in 2 household-level groups (RT) in Rawa Makmur Village. The purposive sampling included 100 respondents, and the research variables were respondent characteristics and 12 PIS-PK indicators. Data analysis was carried out univariately and bivariately through Chi-Square analysis. The research results showed a difference in the number of respondents who had babies in Community I and Community II with Î±0.05 (P-value = 0.022). Generally, there are no statistical differences in almost all healthy family indicators between communities I and II or P-value 0.05. This study concludes that the characteristics of people at the neighboring level tend to be the same in ethnic background, education, marital status, and employment. There is no difference between the 12 indicators of the Healthy Indonesia program and those of the family approach in Community I and Community II.